Extending Puppet - Pastor, Jaime Soriano (Packt Publishing, 2016)
Start pulling the strings of your infrastructure with Puppet x2013; learn how to configure, customize, and manage your systems more intelligentlyAbout This BookExplore the wider Puppet ecosystem of useful toolsDesign and manage your Puppet architecture for optimum performanceWrite more efficient code that keeps your infrastructure more robustWho This Book Is ForIf you are a Puppet user, this book will help you on different levels. If you a beginner, we summarize the key Puppet components and give you the elements to have a broader vision. For more experienced users, you will be surprised by with topics on designing, implementing, adapting, and deploying Puppet architectures. If you are expert, you will find topics and information that is rarely exposed in other books, giving you an insight into Puppet's future and its usage on alternative devices.What You Will LearnLearn the principles of Puppet language and ecosystemExtract the features of Hiera and PuppetDB's power usageExplore the different approaches to Puppet architecture designUse Puppet to manage network, cloud, and virtualization devicesManage and test the Puppet code workflowTweak, hack, and adapt the Puppet extension pointsGet a run through of the strategies and patterns to introduce Puppet automationMaster the art of writing reusable modulesIn DetailPuppet has changed the way we manage our systems, but Puppet itself is changing and evolving, and so are the ways we are using it. To tackle our IT infrastructure challenges and avoid common errors when designing our architectures, an up-to-date, practical, and focused view of the current and future Puppet evolution is what we need. With Puppet, you define the state of your IT infrastructure, and it automatically enforces the desired state.This book will be your guide to designing and deploying your Puppet architecture. It will help you utilize Puppet to manage your IT infrastructure. Get to grips with Hiera and learn how to install and configure it, before learning best practices for writing reusable and maintainable code. You will also be able to explore the latest features of Puppet 4, before executing, testing, and deploying Puppet across your systems. As you progress, Extending Puppet takes you through higher abstraction modules, along with tips for effective code workflow management.Finally, you will learn how to develop plugins for Puppet - as well as some useful techniques that can help you to avoid common errors and overcome everyday challenges.Style and approachThis is a collection of specific information about multiple topics related to Puppet and its ecosystem. Starting from a review of the very basics to more advanced topics, mixing practical advice with important theory and broader perspective, along with implementation details.